2011
DOI: 10.1111/j.1365-2966.2011.19192.x
|View full text |Cite
|
Sign up to set email alerts
|

Seeing measurements using the solar limb - I. Comparison of evaluation methods for the Differential Image Motion Monitor

Abstract: Differential Image Motion Monitors (DIMMs) are used not only for stellar observations but also for solar observations with the limb as the target to evaluate the seeing. In stellar observations, the differential image motions along and perpendicular to the DIMM baseline are consistently employed to evaluate Fried’s parameter. However this is not the case for solar‐limb observations, in which we can measure the image motion only perpendicular to the limb. Therefore the validity of the methods so far proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The time lag of the start of an exposure between the three cameras is less than 8 µs. Assuming the Fried's parameter of 40 mm (Fried 1966;Kawate et al 2011) and wind velocity at the turbulent latitude of 40 m s exactly simultaneous. Motion of the solar image on the slit caused by the local turbulence of air (seeing) was approximately 3 arcsec in amplitude during the run of the observation.…”
Section: Observation and Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The time lag of the start of an exposure between the three cameras is less than 8 µs. Assuming the Fried's parameter of 40 mm (Fried 1966;Kawate et al 2011) and wind velocity at the turbulent latitude of 40 m s exactly simultaneous. Motion of the solar image on the slit caused by the local turbulence of air (seeing) was approximately 3 arcsec in amplitude during the run of the observation.…”
Section: Observation and Image Processingmentioning
confidence: 99%
“…The time lag of the start of an exposure between the three cameras is less than 8 µs. Assuming the Fried's parameter of 40 mm (Fried 1966;Kawate et al 2011) and wind velocity at the turbulent latitude of 40 m s −1 , the time scale of the seeing is approximately equal to 1 ms, that is it is much larger than the synchronization accuracy, and thus the exposures of all three cameras can be regarded as exactly simultaneous. Motion of the solar image on the slit caused by the local turbulence of air (seeing) was approximately 3 arcsec in amplitude during the run of the observation.…”
Section: Observation and Image Processingmentioning
confidence: 99%
“…showed that the typical Fried parameter r 0 at the Hida Observatory was about 4 cm at 600 nm in whole-day and all-season observations 12 . Assuming single ground-layer turbulence with a typical wind speed of 10 m/s, we obtain the Greenwood frequency as f g (typical) =0.427x10/0.04=106.8 (Hz) 13 .…”
Section: System Performancementioning
confidence: 93%
“…In order to obtain accurate polarization signals in ground-based observations, reduction of seeing-induced errors is crucial. A typical Fried's seeing parameter in daytime is several centimeter (Kawate et al 2011) and the seeing changes typically in several milliseconds. Thus, a cycle of the polarization modulation should be completed within several milliseconds.…”
Section: Instruments and Observation Parametersmentioning
confidence: 99%